A Likely Story: Rhetoric and the Determination of Truth in Polybius’ Histories - Farrington, Scott (Histos, 2015)
I argue that Polybius demands that a central duty of the historian should be to employ rhetoric to determine which sources are credible, define the course of past events, and convince the reader that the resulting historical narrative is true. Polybius asserts that the historian must 'teach and persuade', so I examine the use of this collocation in other prose authors and rhetorical treatises. I also examine the ways in which Polybius behaves both as a dikast, who must judge the quality of competing narratives, and as an orator who must convince his audience to accept his determinations; and I consider certain rhetorical strategies employed by Polybius to these ends. I conclude that Polybius openly applied rhetoric to historical narrative with the expectation that it would make the narrative both more accurate and more credible.